1982
DOI: 10.1002/eji.1830121010
|View full text |Cite
|
Sign up to set email alerts
|

Human T cell clones specific for tetanus toxoid: Characterization of antigen specificity and HLA restriction

Abstract: T cell blasts isolated from six-day cultures of peripheral blood mononuclear cells stimulated with tetanus toxoid (TT) were cloned in a two-layer agar system in the presence of autologous irradiated PBM (iPBM) and TT. Colonies were individually isolated and expanded in interleukin 2-containing medium. The antigen specificity of three T cell clones was attested by their capacity to proliferate under restimulation by TT and not by an unrelated antigen. The clones were specific for either the alpha or the beta ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The phenotype analysis of the clones showed that all but one of the clones were CD4+. Predominance of CD4+ clones has also been reported with' other antigens like tetanus toxoid (18), influenza virus (8), and Chlamydia trachomatis (16). The clones'were also expressing NG1 and NG2 subsets of HLA-DR, DP-associated antigens, and DQ locus antigens.…”
Section: Discussionmentioning
confidence: 70%
“…The phenotype analysis of the clones showed that all but one of the clones were CD4+. Predominance of CD4+ clones has also been reported with' other antigens like tetanus toxoid (18), influenza virus (8), and Chlamydia trachomatis (16). The clones'were also expressing NG1 and NG2 subsets of HLA-DR, DP-associated antigens, and DQ locus antigens.…”
Section: Discussionmentioning
confidence: 70%
“…Clone D106 (a kind gift from M. Agrapart and J. J. Ballet, Hopital St. Louis, Paris) is a human CD4-positive, CD3-positive, CD8-negative T-cell clone that specifically responds to tetanus toxoid when cocultured with autologous macrophages (11). Clone SPB21 is a CD4-positive, CD3-positive, CD8-negative human T-cell clone that was selected through specific proliferation triggered by anti-T-cell receptor (TCR)-CD3 monoclonal antibody (mAb) 3D6 (12).…”
Section: Introductionmentioning
confidence: 99%
“…No human monoclonal antibodies which are specific for light chain have been described yet, although most monoclonal antibodies have not been tested for this property (3,11). However, light chain-specific human T-cell clones have been described (22).…”
Section: Discussionmentioning
confidence: 99%